PEMBERDAYAAN IBU RUMAH TANGGA DALAM MENINGKATKAN EKONOMI KELUARGA DENGAN BERIWIRAUSAHA SECARA MANDIRI DI RT 03 RW 12 KELURAHAN TANGKERANG TENGAH - Faizah Kamilah; Zulia Khairani; Efrita Soviyanti (Komunitas Manajemen Kompetitif, 2026)
This Community Service activity aims to provide knowledge about entrepreneurship and its characteristics among the women in RT 03/RW 12, Tangkerang Tengah Village, Marpoyan Damai District. The community service activity employed lectures and a question-and-answer session. The lecture method was used to convey general knowledge about possible initiatives. Questions and answers were used to supplement any areas not covered by the lecture method. This training involved lecturers from the Accounting and Management Department, working with the women in RT 03/RW 12, Tangkerang Tengah Village, Marpoyan Damai District, as the target subjects.